Ramadan diurnal intermittent fasting is associated with significant plasma metabolomics changes in subjects with overweight and obesity: A prospective cohort study - Madkour, Mohamed; Giddey, Alexander D.; Soares, Nelson C.; Semreen, Mohammad H.; Bustanji, Yasser; Zeb, Falak; Halwani, Rabih; Faris, MoezAlIslam E. (Frontiers in Nutrition, 2023)
During the holy month of Ramadan, adult healthy Muslims are mandated to abstain from dawn to sunset, with free eating night hours that may extend up to 12 hours. The current work was designed to investigate the metabolomics changes incurred upon the observance of Ramadan diurnal intermittent fasting (RDIF). Twenty-five metabolically healthy participants with overweight and obesity (7 females and 18 males, with a mean age of 39.48±10.0 years) were recruited for the study and were followed before and at the end of RDIF month. Dietary, anthropometric, biochemical, and physical activity assessments were performed before and at the end of the fasting month. The metabolomic assay was performed using liquid chromatography-mass spectrometry for the two-time points. Metabolomics assay revealed a significant reduction in a few metabolites. The analysis revealed that 27 metabolites differed significantly (P<0.05) between pre-and post-RDIF. Among the differentially abundant metabolites, 23 showed a decrease with fasting, these included several amino acids such as aspartame, tryptophan, phenylalanine, histidine, and other metabolites including valeric acid, and cortisol. On the other hand, only four metabolites showed increased levels with RDIF including traumatic acid, 2-pyrrolidinone, PC(18:1(9Z)/18:1(9Z)), and L-sorbose. The MetaboAnalyst® platform reported that the top enriched metabolic pathways included: (1) histidine metabolism; (2) folate biosynthesis (3) phenylalanine, tyrosine, and tryptophan biosynthesis; (3) aminoacyl-tRNA biosynthesis; (3) caffeine metabolism (4) vitamin B6 metabolism; and several other pathways relating to lipid metabolisms such as arachidonic acid metabolism, glycerophospholipid metabolism, and linoleic acid metabolism. In conclusion, RDIF entails significant changes in various metabolic pathways that reflect different dietary and lifestyle behaviors practiced during the fasting month.